Creative Music Therapy and Neurodevelopmental Outcomes in Pre-term Infants at 2 Years: A Randomized Controlled Pilot Trial - Haslbeck, Friederike Barbara; Bucher, Hans Ulrich; Bassler, Dirk; Hagmann, Cornelia; Natalucci, Giancarlo (Frontiers in Pediatrics, 2021)
Impaired neurodevelopment is increasingly recognized as a major health issue in children born prematurely. Creative music therapy (CMT) intends to prevent and or reduce neurobehavioral deficits in preterm infants using musical stimulation and socio-emotional co-regulation. We conducted a randomized, clinical pilot CMT trial to test feasibility and to examine long-term neurodevelopmental outcomes in preterm infants. (NCT02434224: https://clinicaltrials.gov/ct2/show/NCT02434224). Eighty-two preterm infants were randomized either to CMT or standard care. A specially trained music therapist provided family-integrating CMT via infant-directed singing during hospitalization. Fifty-six infants underwent follow-up at two years of corrected age. No significant beneficial nor adverse effects of CMT were identified in routine clinical neurodevelopmental measures (Bayley-III Scales of Infant and Toddler Development and the standardized neurological examination). Longer term follow-up (five years) and larger future studies are recommended to elucidate possible long-term effects of music in relation to more sensitive outcomes including executive function, detailed language processing and social-emotional development.